The American city - Islam, Nazrul, 1941-; Alam, Fakrul; Bangladesh Association for American Studies (Dhaka : Bangladesh Association for American Studies, 1991)
City from the perspectives of social science and literature.
"Collection of papers read at the Annual Conference of Bangladesh Association for American Studies (BAAS) held in 1989"--From the editors.
Includes bibliographical references.
Keywords: Cities and towns -- United States -- Congresses